2022
DOI: 10.1186/s12944-022-01643-9
|View full text |Cite
|
Sign up to set email alerts
|

Delta-5® oil, containing the anti-inflammatory fatty acid sciadonic acid, improves skin barrier function in a skin irritation model in healthy female subjects

Abstract: Background Sciadonic acid (SA) is an anti-inflammatory fatty acid displacing arachidonic acid (ARA) from specific phospholipid pools, thus modulating downstream pro-inflammatory lipid mediators. Its novel anti-inflammatory actions have been studied in vitro, in pre-clinical models, and stemming from testimonials, after topical- and oral application. It has not been tested in a formal clinical study for topical benefits previously. Skin barrier layer was our focus as it has a critically importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Palmitic acid, lauric acid and oleic acid in free fatty acids increase the release of antimicrobial peptides in the sebaceous glands, thus achieving an antimicrobial effect and preventing the entry of external harmful substances into the organism 22 . Sciadonic acid (SA), an anti‐inflammatory fatty acid analogue of arachidonic acid, has also been shown to have anti‐inflammatory effects in human skin, accelerating stimulus‐induced healing and improving skin barrier function under controlled clinical conditions 23,24 . Triglyceride and fatty acids are important components of sebaceous lipids (Sebaceous lipids), accounting for 57% of their composition, freshly secreted sebum does not contain fatty acids, but is produced by the hydrolysis of triglyceride by bacteria and yeast on the surface of the skin after sebum secretion 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Palmitic acid, lauric acid and oleic acid in free fatty acids increase the release of antimicrobial peptides in the sebaceous glands, thus achieving an antimicrobial effect and preventing the entry of external harmful substances into the organism 22 . Sciadonic acid (SA), an anti‐inflammatory fatty acid analogue of arachidonic acid, has also been shown to have anti‐inflammatory effects in human skin, accelerating stimulus‐induced healing and improving skin barrier function under controlled clinical conditions 23,24 . Triglyceride and fatty acids are important components of sebaceous lipids (Sebaceous lipids), accounting for 57% of their composition, freshly secreted sebum does not contain fatty acids, but is produced by the hydrolysis of triglyceride by bacteria and yeast on the surface of the skin after sebum secretion 25 .…”
Section: Discussionmentioning
confidence: 99%
“… 22 Sciadonic acid (SA), an anti‐inflammatory fatty acid analogue of arachidonic acid, has also been shown to have anti‐inflammatory effects in human skin, accelerating stimulus‐induced healing and improving skin barrier function under controlled clinical conditions. 23 , 24 Triglyceride and fatty acids are important components of sebaceous lipids (Sebaceous lipids), accounting for 57% of their composition, freshly secreted sebum does not contain fatty acids, but is produced by the hydrolysis of triglyceride by bacteria and yeast on the surface of the skin after sebum secretion. 25 Sebum has a role in moisturizing as well as maintaining and restoring the skin barrier, and in addition triglycerides in skin lipids can inhibit the expression of matrix metalloproteinase‐1 and inflammation‐associated protein cyclooxygenase‐2 (COX‐2) and interleukin‐1b (IL‐1b) after UV irradiation, suggesting that triglyceride play an important role in skin repair.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of a trans-5 double bond into the molecule of linoleic acid, 18:2n-6, results in columbinic acid, 18:3Δ5trans,9cis,12cis, having attractive biological properties [ 147 ]. Experiments with essential FA-deficient rats, have shown that the columbinic acid is effective in maintaining the proper epidermal layer and improves the fertility of rats, while the inhibition of prostaglandin synthesis has a beneficial effect, since inflammation and the thrombotic tendency are reduced [ 148 ].…”
Section: Echinoderm Fatty Acids As Bioactive Compoundsmentioning
confidence: 99%
“…Improvement in the barrier function would benefit the treatment of dermatitis, acne, eczema, and skin scarring. Oil with Δ5 NMI FAs has a potential to maintain healthy, moisturized skin and to improve the skin structure, elasticity, and firmness [ 148 ].…”
Section: Echinoderm Fatty Acids As Bioactive Compoundsmentioning
confidence: 99%